Neo-Splicetopes in Tumor Therapy: A Lost Case? - Kloetzel, Peter M. (Frontiers in Immunology, 2022)
Proteasome generates spliced peptides by ligating two distant cleavage products in a reverse proteolysis reaction. The observation that CD8+ T cells recognizing a spliced peptide induced T cell rejection in a melanoma patient following adoptive T cell transfer (ATT), raised some hopes with regard to the general therapeutic and immune relevance of spliced peptides. Concomitantly, the identification of spliced peptides was also the start of a controversy with respect to their frequency, abundancy and their therapeutic applicability. Here I review some of the recent evidence favoring or disfavoring an immune relevance of splicetopes and discuss from a theoretical point of view the potential usefulness of tumor specific splicetopes and why against all odds it still may seem worth trying to identify such tumor and patient-specific neosplicetopes for application in ATT.